Anterior Upper Teeth Golden Proportion Analysis with Millimetric Templates: An Invention Developed at Londrina State University - Adriana De Oliveira Silva; Hebert Samuel Carafa Fabre; Wagner José Silva Ursi; Márcio Grama Hoeppner; Anna Laura Morais Do Amaral (International Journal of Dentistry)
In order to achieve aesthetic and harmonious smile results, the use of anterior upper teeth golden proportion concepts represents reliable and scientific based guidelines. However, measuring, recording and analysing teeth and smiles biometric values proves to be a clinical and laboratory routine chalenge, once it is time consuming and demands additional especific math calculus or formulas. The aim of this paper is present an invention, “anterior upper teeth golden proportion millimetric templates,” a set of instruments fabricated in order to achieve precise and fast millimetric measures, once they present predefined geometrical drawings and diagrams. Currently, when planning aesthetic tooth size modifications treatments, tools are used as pachymeters, dry edge compass, or some softwares. Most of times this strategy relies on professional expertise and intuiton, which shows to be limitating factors with the need of trial-and-error training and an accurate critical and artistic sense. Unfortunately, this is not inherent to all professionals, especially undergraduate dental school students. Thus, the templates bring differentials and advantages, being versatile and convenient, allowing countless clinical and laboratory uses, even over a cellphone or a computer screen. An excellent diagnostic aid providing ideal teeth proportions and positioning, increasing the chances of success in dental treatment planning.